CP-25, a compound derived from paeoniflorin: research advance on its pharmacological actions and mechanisms in the treatment of inflammation and immune diseases - Yang Xue-zhi; Wei Wei (Acta Pharmacologica Sinica, 2020)
Total glycoside of paeony (TGP) has been widely used to treat inflammation and immune diseases in China. Paeoniflorin (Pae) is the major active component of TGP. Although TGP has few adverse drug reactions, the slow onset and low bioavailability of Pae limit its clinical use. Enhanced efficacy without increased toxicity is pursued in developing new agents for inflammation and immune diseases. As a result, paeoniflorin-6′-O-benzene sulfonate (CP-25) derived from Pae, is developed in our group, and exhibits superior bioavailability and efficacy than Pae. Here we describe the development process and research advance on CP-25. The pharmacokinetic parameters of CP-25 and Pae were compared in vivo and in vitro. CP-25 was also compared with the first-line drugs methotrexate, leflunomide, and hydroxychloroquine in their efficacy and adverse effects in arthritis animal models and experimental Sjögren’s syndrome. We summarize the regulatory effects of CP-25 on inflammation and immune-related cells, elucidate the possible mechanisms, and analyze the therapeutic prospects of CP-25 in inflammation and immune diseases, as well as the diseases related to its potential target G-protein-coupled receptor kinases 2 (GRK2). This review suggests that CP-25 is a promising agent in the treatment of inflammation and immune diseases, which requires extensive investigation in the future. Meanwhile, this review provides new ideas about the development of anti-inflammatory immune drugs.